2020
DOI: 10.1186/s40478-020-01018-0
|View full text |Cite
|
Sign up to set email alerts
|

Defining novel functions for cerebrospinal fluid in ALS pathophysiology

Abstract: Despite the considerable progress made towards understanding ALS pathophysiology, several key features of ALS remain unexplained, from its aetiology to its epidemiological aspects. The glymphatic system, which has recently been recognised as a major clearance pathway for the brain, has received considerable attention in several neurological conditions, particularly Alzheimer's disease. Its significance in ALS has, however, been little addressed. This perspective article therefore aims to assess the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 225 publications
(275 reference statements)
0
15
0
Order By: Relevance
“…In some versions of the glymphatic hypothesis the perivenous outflow is thought to enter the subarachnoid spaces where it mixes with CSF (e.g. [ 36 , 76 , 90 , 91 ]. These versions can easily be modified and extended to include outflow via white matter tracts leading to the ventricles [ 60 , 64 , 92 ].…”
Section: The Development Of the Glymphatic Hypothesismentioning
confidence: 99%
“…In some versions of the glymphatic hypothesis the perivenous outflow is thought to enter the subarachnoid spaces where it mixes with CSF (e.g. [ 36 , 76 , 90 , 91 ]. These versions can easily be modified and extended to include outflow via white matter tracts leading to the ventricles [ 60 , 64 , 92 ].…”
Section: The Development Of the Glymphatic Hypothesismentioning
confidence: 99%
“…Of note is the possibility already suggested by others that the CSF circulation could constitute a pathway for the spread of pathology, which various lines of evidence are now hinting at ( Smith et al, 2015 ; Gomez-Pinedo et al, 2018 ; Mishra et al, 2020 ). This could in turn help to potentially account for many of the unexplained features of ALS, one of which is the non-contiguous spreading pattern occasionally observed ( Smith et al, 2015 ; Ng Kee Kwong et al, 2020b ).…”
Section: Als As a Proteinopathymentioning
confidence: 99%
“…48 The abnormal expression of AQP4 has been associated with altered blood-brain barrier integrity in ALS sufferers, as well as impaired potassium homeostasis and glutamate dysregulation. 76,77 Based on these observations, we examined the expression of both KCNJ10 and AQP4 in human iPSC-derived VS astrocytes. We observed that these preparations express low levels of AQP4, suggesting that they should be suited to investigate the functional impact of AQP4 up-regulation, a situation that would be expected in astrocytes generated from iPSCs derived from ALS patients.…”
Section: Human Ipsc-derived Ventral Spinal-like Astrocytes Have Properties Of Physiological Astrocytesmentioning
confidence: 99%